1996
DOI: 10.1016/0735-1097(96)00071-x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of inadequate compensatory enlargement to development of human coronary artery stenosis: An in vivo intravascular ultrasound study

Abstract: Compensatory enlargement commonly (54%) occurs at stenotic coronary lesions. However inadequate compensatory enlargement results in a substantial amount (39%) of the lumen area reduction in 26% of primary coronary artery lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
2
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(106 citation statements)
references
References 13 publications
2
99
2
3
Order By: Relevance
“…3,10 In this study, however, we found no relation between remodeling in atherosclerosis and remodeling or late lumen loss after balloon angioplasty. Whether this result is specific for the animal model used in this investigation remains to be determined, although as mentioned previously remodeling in this model seems to parallel remodeling in human coronary arteries closely.…”
Section: Remodeling In De Novo Atherosclerosis and Remodeling After Bcontrasting
confidence: 80%
See 2 more Smart Citations
“…3,10 In this study, however, we found no relation between remodeling in atherosclerosis and remodeling or late lumen loss after balloon angioplasty. Whether this result is specific for the animal model used in this investigation remains to be determined, although as mentioned previously remodeling in this model seems to parallel remodeling in human coronary arteries closely.…”
Section: Remodeling In De Novo Atherosclerosis and Remodeling After Bcontrasting
confidence: 80%
“…[1][2][3] In contrast to enlargement, shrinkage of an atherosclerotic artery enhances arterial obstruction that is caused by atherosclerotic plaque. 2,3 Remodeling after balloon angioplasty has also been reported and has been recognized as a major determinant of restenosis. After balloon angioplasty, shrinkage seems to be the predominant, although certainly not the only, mode of remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, these IVUS studies have also shown that negative remodeling (shrinkage of EEM CSA at the lesion site) is observed in 15% to 34% of stenotic lesions and, along with the plaque accumulation, contributes to luminal narrowing. 9,10 Studies correlating IVUS and clinical findings have suggested that positive remodeling lesions may be more biologically active and negative remodeling lesions more inert.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] More recently, pathology and IVUS studies have also shown that compensatory enlargement is often inadequate to preserve lumen size completely, and that some vessels may not remodel or, paradoxically, may even shrink at the lesion site. [19][20][21][22][23][24][25][26] Positive remodeling and larger plaques have been associated with acute coronary syndromes. However, information is lacking on the relationship between coronary arterial remodeling and the different types of acute coronary syndromes.…”
Section: Introductionmentioning
confidence: 99%